Remarks on the Experimental Turn in the Study of Scalar Implicature, Part II. Issue 9 (September 2014) - Chemla, Emmanuel; Singh, Raj
Abstract In Part I, we have introduced two of the main approaches to scalar implicature: the Gricean approach and the grammatical approach. We have argued that although they rely on conceptually different views about the phenomenon, they share various insights, and we argued that their empirical differences were more subtle than what one may have expected. In this second part of this review paper, we will sample some experimental results with two goals in mind. First, we will exemplify some simplifications that are found in the literature and examine the consequences of these simplifications on the interpretability of experimental results. Second, we will suggest future directions that the experimental turn might consider exploring, directions that seem to us to have the potential to illuminate the richness of the competing theories and the potential to dissociate or improve them.